UPAYA OXFAM DALAM MENANGANI FEMINISASI KEMISKINAN DI INDONESIA (2017-2019) - Citra Ayu Kinanti (2023)
Feminist approaches seek to reconstruct international relations in a more gender-neutral way. Feminism makes an essential contribution to the discipline of international relations by evaluating gender bias in traditional theory and practice. The tendency to ignore the social relations of gender has created unequal relations between women and men in political-economic structures at both local and global levels. This has made women more vulnerable to economic insecurity than men. The gap between women and men trapped in the cycle of poverty has illustrated a portrait of the feminization of poverty, where women are disproportionately represented in the phenomenon of world poverty. The feminization of poverty occurs due to hierarchical injustice in the constellation of the international political economy. The limited access and socio-economic barriers have ensnared women in the complexity of structural poverty. In efforts to alleviate global poverty, INGOs are important actors in the distribution of foreign aid and global philanthropy. Oxfam as an INGO engaged in global development issues has a significant role in advancing the right to a decent livelihood. Oxfam encourages the empowerment of women to participate in all aspects of economic, social, cultural and political life. Thus, this research aims to understand Oxfam's efforts in dealing with the feminization of poverty in Indonesia using the lens of liberal feminism. The results of this research analysis will explain the alignment of Oxfam's feminist perspective with the ideas of liberal feminism regarding gender inequality in development in Indonesia.